THE EFFECT OF GUIDED INQUIRY LABORATORY ACTIVITY WITH VIDEO EMBEDDEDON STUDENTS' UNDERSTANDING AND MOTIVATION IN LEARNING LIGHT AND OPTICS - Tina Afriani, - (2019)
This research aims to investigate the effect of guided inquiry laboratory activity with video embedded on students' understanding and students' motivation in learning lights and optics topic. The method used in this research was pre-experiment. Sampling technique used in this research was convenience sampling and the samples were taken from grade 8 in one of junior high school in Bandung. The sample was 20 students. The class implemented guided inquiry laboratory activity with video embedded in learning light and optics.The students' understanding was measured using test given at pretest and post-test while students' motivation was calculated using software ministeps (RASCH Model). The t-test paired sample also was performed on the average level of 95% to identify the significant difference of students' understanding before and after the implementation of guided inquiry laboratory activity with video embedded. The results of this research show that the use of guided inquiry laboratory with video embedded gives improvement of students understanding. Eventhough the value of n-gain is 0.264 (categorized as low level), the statistical test shows that there is significant difference between students understanding before and after the implementation of guided inquiry laboratory activity with video embedded.There are 15 students from 20 students who are motivated in learning light and optics by using guided inquiry laboratory activity with video embedded. Almost all statements related to students motivation toward science learning can be approved by students. It means that students are motivated by the implementation of guided inquiry laboratory activity with video embedded.--------Penelitian ini bertujuan untuk mengetahui pengaruh inkuiriter bombing dalam kegiatan laboratorium dengan peayangan video terhadap pemahaman dan motivasi siswa dalam pembelajaran cahaya dan alat optik. Metode yang digunakan dalam penelitian ini adalah pre-experiment. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah convenience sampling dan sampel diambil di kelas 8 dari salah satu sekolah menengah pertama di Bandung. Sampel adalah 20 siswa. Kelas diterapkan inkuiri terbimbing dalam kegiatan laboratorium dengan video yang tertanam dalam pembelajaran cahaya dan alat optik. Pemahaman siswa diukur dengan menggunakan tes yang diberikan pada saat pretest dan post-test sementara motivasi siswa dihitung dengan menggunakan perangkat lunak ministeps (RASCH Model). Paired sample t-test juga dilakukan pada tingkat rata-rata 95% untuk mengidentifikasi perbedaan signifikan dari pemahaman siswa sebelum dan sesudah pelaksanaan inkuiri terbimbing dalam kegiatan laboratorium dengan penayangan video. Hasil penelitian ini menunjukkan bahwa penggunaan inkuiri terbimbing dalam kegiatan laboratorium dengan penayangan video memberikan peningkatan pemahaman siswa. Meskipun nilai n-gain adalah 0.264 (dikategorikan sebagai level rendah), uji statistic menunjukkan bahwa ada perbedaan yang signifikan antara pemahaman siswa sebelum dan sesudah tritmen. 75% siswa termotivasi dalam pembelajaran cahaya dan alat optic dengan menggunakan inkuiri terbimbing dalam kegiatan laboratorium dengan penayangan video. Hampir semua pernyataan yang terkait dengan motivasi siswa terhadap pembelajaran sains dapat disetujui oleh siswa. Ini berarti bahwa siswa termotivasi oleh pelaksanaan inkuiri terbimbing dalam kegiatan laboratorium dengan penayangan video.